Comparison of cost-effectiveness and postoperative outcomes following integration of a stiff shaft glidewire into percutaneous nephrolithotripsy. (August 2021) - Valadon, Crystal; Abedali, Zain A.; Nottingham, Charles U.; Large, Tim; Krambeck, Amy E.
Aims: To analyze the cost effectiveness of integrating a stiff shaft glidewire (SSGW) in percutaneous nephrolithotripsy (PCNL) relative to standard technique (ST). This is prudent because healthcare providers are experiencing increased pressure to improve procedure-related cost containment. Methods: ST for PCNL at our institution involves a hydrophilic glidewire during initial percutaneous access and then two new stiff shaft wires. The SSGW is a hydrophilic wire used for initial access and the remainder of the procedure. We collected operating room (OR) costs for all primary, unilateral PCNL cases over a 5-month period during which ST for PCNL was used at a single institution with a single surgeon and compared with a 6-month period during which a SSGW was used. Mean costs for each period were then compared along with stone-free rates and complications. Results: We included 17 total cases in the ST group and 22 in the SSGW group. The average operating room supply cost for the ST group was 1937.32 and 1559.39 in the SSGW group. The net difference of 377.93 represents a nearly 20% decrease in cost. This difference was statistically significant ( p = 0.031). There was no difference in postoperative stone-free rates (82.4% versus 86.4%, p = 1.0, respectively) or complications (23.5% versus 13.6%, p = 0.677, respectively) between ST and SSGW groups. Conclusion: Transitioning to a SSGW has reduced OR supply cost by reducing the number of supplies required. The change in wire did not affect stone-free rates or complications.